Dialogue between nutrition and reproduction: preliminary exploration of sperm quality response to high-fat diet in mice - Jiang, Yali; Zhang, Wenge (Frontiers in Cell and Developmental Biology, 2026)
BackgroundHigh-fat diets are known to affect semen quality, potentially through metabolic and cellular stress mechanisms.ObjectivesThis study investigates the impact of a high-fat diet on semen quality in male mice and identifies the underlying mechanisms involved.Materials and methodsThirty male C57BL/6J mice were randomly assigned to a control diet (CD) or HFD for 12 weeks. Sperm parameters and fertility were assessed by computer-assisted sperm analysis and mating trials. Testicular oxidative stress indices, autophagy- and apoptosis-related proteins were analyzed by biochemical assays and Western blot. Mitophagy (LC3B–Grp75 co-localization), tissue morphology (H&E, TUNEL, electron microscopy) and sperm DNA damage (DNA fragmentation index, 8-hydroxy-2′-deoxyguanosine [8-OHdG]) were further evaluated. Serum lipids and testosterone were measured by enzymatic assays and ELISA.ResultsHFD mice developed obesity, dyslipidemia, reduced testosterone, marked decreases in sperm count, progressive motility and normal morphology, and complete loss of fertility. Region-specific molecular alterations were observed along the reproductive tract: in epididymal caput, Beclin-1 and LC3B were upregulated and p62 downregulated, indicating enhanced autophagic flux; in cauda epididymis, pro-apoptotic markers increased and Bcl-2 decreased, consistent with augmented apoptosis; in testis, ATG5, Beclin-1, caspase-3 and Apaf-1 were elevated. HFD also increased testicular ROS and MDA, reduced SOD activity and mitochondrial membrane potential, and elevated sperm apoptosis, DNA fragmentation and 8-OHdG.ConclusionHFD induces a pathogenic cascade—oxidative stress, disrupted autophagy/mitophagy, and mitochondrial apoptosis-that collectively impair spermatogenesis and male fertility. Therapeutic strategies targeting antioxidant defenses, autophagic flux, and mitophagy may ameliorate obesity-related reproductive dysfunction.